(3GdSjQ hGdSdhc Edi edc Gdedhcs - (3bGSe Hf UdGM GdOjf GdNGfj GdMdHj,J (B1109 (3g` s ((3MSf Gdecfi HGHf GdNWjH s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdMeO ddg GdPi CgH HMceJg CSQGQ PGJg hHYO aEf Sdhc WQjb GdMb ef CNdGb GdCfHjGA hGdeQSdjf acPdc gPG GdSdGc dGHO dg ef eQTO YGQa HgPG GdWQjb hSejJgG GdSjQ hGdSdhc Edi edc Gdedhc s
(3BNQgG (B:s
(3hCeG GdYGQahf GdCbhjGA aEfg dGjVdge EdG HeG jfGSHge eeG PcQ ef CfhGY GdEVdGd hUdi Gddg JYGdi Ydi CTQ GdCfHjGA hGdeQSdjf hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B104 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B833s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B34s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs